Communication and hidden action: A credit market experiment - Martin Brown; Jan Schmitz; Christian Zehnder (Swiss National Bank, Study Center Gerzensee, 2023)
We study the impact of pre-contractual communication on market outcomes when economic relationships are subject to hidden action. Our experiment is framed in a credit market context and borrowers (second movers) can communicate with lenders (first movers) prior to entering the credit relationship. Communication reduces moral hazard (strategic default) and increases trust (credit provision) in an environment where opportunistic behavior by borrowers is revealed ex-post to lenders. By contrast, in an environment where strategic defaults are hidden behind a veil of uncertainty, we find a substantially weaker impact of communication. Borrowers are more likely to renege on repayment promises when they can hide opportunistic behavior from lenders. As a consequence, lenders extend less credit to borrowers who promise to repay. Hidden action undermines the positive effect of communication on market outcomes. Our findings have implications for the design of contracts and how to structure relationships with a risk of hidden action: for precontractual communication to unfold its full potential it needs to go hand-in-hand with post-contractual monitoring.
Keywords: G21; G41; C91; 330; pre-contractual Communication; Hidden Action; Trust Game; Credit Market